2017
DOI: 10.3390/ijms18040834
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Melatonin on the In Vitro Maturation of Sheep Oocytes and Its Relation to Melatonin Receptors

Abstract: (1) Background: The binding sites of melatonin, as a multifunctional molecule, have been identified in human, porcine, and bovine samples. However, the binding sites and mechanisms of melatonin have not been reported in sheep; (2) Methods: Cumulus–oocyte complexes (COCs) were cultured in TCM-199 supplemented with melatonin at concentrations of 0, 10−3, 10−5, 10−7, 10−9, and 10−11 M. Melatonin receptors (MT1 and MT2) were evaluated via immunofluorescence and Western blot. The effects of melatonin on cumulus cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 60 publications
4
56
0
Order By: Relevance
“…Studies using cell cultures and animals have revealed the beneficial effects of melatonin on oocyte maturation, development of growing follicles, embryonic development, and other reproduction activities in vitro and in vivo . Beneficial effects on the in vitro maturation of sheep oocytes and an increased ratio of vitrified sheep blastocysts have been demonstrated following melatonin application in vitro . Melatonin promotes oocyte maturation, and improves their subsequent fertilization rate in humans by reducing oxidative stress within oocytes .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using cell cultures and animals have revealed the beneficial effects of melatonin on oocyte maturation, development of growing follicles, embryonic development, and other reproduction activities in vitro and in vivo . Beneficial effects on the in vitro maturation of sheep oocytes and an increased ratio of vitrified sheep blastocysts have been demonstrated following melatonin application in vitro . Melatonin promotes oocyte maturation, and improves their subsequent fertilization rate in humans by reducing oxidative stress within oocytes .…”
Section: Introductionmentioning
confidence: 99%
“…The melatonin works as an opposing oestrogen, hence enhancing immune system response (Sanchez‐Barcelo et al., ). It is a widely known fact that melatonin controls ovarian actions through the directive of gonadotrophin proclamation in the hypothalamus–pituitary gland axis through its particular receptors (Tan et al., ; Tian et al., ).…”
Section: Research Progress Of Action Mechanism Of Melatoninmentioning
confidence: 99%
“…Melatonin and its metabolites act as dominant antioxidants, which can possibly prevent early ovarian miscarriage. From the current literature of background work (Arendt, ; Banach, Gurdziel, Jedrych, & Borowicz, ; De Leersnyder et al., ; Duffield et al., ; El‐Mokadem et al., ; Grossman, Laudon, & Zisapel, ; Henriquez et al., ; Hillier, ; Howard & Lutterschmidt, ; Hu, Christian, Sipes, & Hoyer, ; Jan et al., ; Kang et al., ; Koppisetti et al., ; Li et al., ; Maganhin et al., ; Mukherjee et al., ; Peres, Masruha, Zukerman, Moreira‐Filho, & Cavalheiro, ; Pierce & Parsons, ; Reiter et al., ; Reiter et al., ; Rozen, ; Saenz De Miera et al., ; Sambrook & Russell, ; Sanchez‐Barcelo et al., ; Singh & Haldar, ; Singh & Jadhav, ; Tian et al., ; Ubuka et al., ; Valenzuela, Vera, Venegas, Pino, & Lagunas, ; Vijayalaxmi, Reiter, Herman, & Meltz, , ; Weems, Goodman, & Lehman, ; Yoshimura, ; Yumnamcha et al., ), there has been extensive progress of action mechanism of melatonin and its related areas. For instance, the protection of gametes and embryos (Voiculescu et al., ), the response of clock genes (Saenz De Miera et al., ; Vriend & Reiter, ) and the immune‐neuroendocrine interactions (Vijayalaxmi et al., ) reconcile seasonal variations in immune functions and the silencing or blockage of genes.…”
Section: Research Progress Of Action Mechanism Of Melatoninmentioning
confidence: 99%
See 2 more Smart Citations